2011
DOI: 10.1002/yea.1843
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive phenotypic analysis of single‐gene deletion and overexpression strains of Saccharomyces cerevisiae

Abstract: We quantified the growth behaviour of all available single-gene deletion and overexpression strains of budding yeast. Genome-wide analyses enabled the extraction of the genes and identification of the functional categories for which genetic perturbation caused the change of growth behaviour. Statistical analyses revealed defective growth for 646 deletion and 1302 overexpression strains. We classified these deleted and overexpressed genes into known functional categories, and identified several functional categ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
94
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(120 citation statements)
references
References 37 publications
23
94
0
Order By: Relevance
“…Overexpression of TAF1, TAF3, TAF7, TAF8, and TAF14 resulted in dominant negative growth phenotypes, consistent with published results (75). As expected, overexpression of TAF2 could complement growth for all taf2 ts variants ( Fig.…”
Section: Journal Of Biological Chemistry 22723supporting
confidence: 91%
“…Overexpression of TAF1, TAF3, TAF7, TAF8, and TAF14 resulted in dominant negative growth phenotypes, consistent with published results (75). As expected, overexpression of TAF2 could complement growth for all taf2 ts variants ( Fig.…”
Section: Journal Of Biological Chemistry 22723supporting
confidence: 91%
“…Most highly expressed genes in yeast are not subject to complete dosage compensation when mutated (34), but feedback at the gene level may be particularly common among transcription factors (35,36). In light of our evidence that feedback may serve to constrain the deleterious effects of misregulation among transcription factors, a model invoking especially strong pressures for such feedback control would be consistent with the extreme overexpression toxicity observed across transcription factors in yeast (31). The emerging picture is one in which both gene-and pathway-level feedback, at transcription factor genes and elsewhere in the yeast network, may be key elements of the architecture that mediates buffering of genetic change.…”
Section: Discussionsupporting
confidence: 57%
“…S3). To test the relationship between expression homeostasis and feedback more generally, we used growth rates of yeast strains manipulated to overexpress each transcription factor in turn (31). We first integrated these data with the results of our reporter-based screen for feedback among transcription factors (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with this notion, switch genes are significantly enriched for dosagesensitive genes reported to result in cell cycle delay and/or growth defects when overexpressed. 65,66 Moreover, analysis of transcription induction upon replication stress showed that this group of genes is enriched for genes that are upregulated during replication stress conditions. 13,51 Switch Genes as DosageSensitive Checkpoint Effectors TOS genes.…”
Section: "Switch Genes:" a New Class Of G 1 /S Cell Cycle Genesmentioning
confidence: 99%
“…69 TOS4, MCD1, SWE1 and ACM1 are cell cycle-regulated, and, corroborating our hypothesis that switch genes expression needs to be tightly regulated, overexpression of these genes was linked to growth defect and/or cell cycle arrest. 65,66 Further analysis of the other switch genes, such as the TOS genes and eight putative ORFs, will show their potential role as checkpoint effectors.…”
Section: "Switch Genes:" a New Class Of G 1 /S Cell Cycle Genesmentioning
confidence: 99%